2021
DOI: 10.3390/ijms22063026
|View full text |Cite
|
Sign up to set email alerts
|

The MIR-Domain of PbbHLH2 Is Involved in Regulation of the Anthocyanin Biosynthetic Pathway in ”Red Zaosu” (PyrusBretschneideri Rehd.) Pear Fruit

Abstract: The N-terminal of Myc-like basic helix-loop-helix transcription factors (bHLH TFs) contains an interaction domain, namely the MYB-interacting region (MIR), which interacts with the R2R3-MYB proteins to regulate genes involved in the anthocyanin biosynthetic pathway. However, the functions of MIR-domain bHLHs in this pathway are not fully understood. In this study, PbbHLH2 containing the MIR-domain was identified and its function investigated. The overexpression of PbbHLH2 in ”Zaosu” pear peel increased the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Direct interactions of MYB or bHLH alone with promoters of structural genes has not been previously shown. Rather, they regulate ABP structural genes by forming MBW protein complexes ( Li et al., 2021b ; Yan et al., 2021 ). Similarly, we found DhMYB2 and DhbHLH1 alone are not sufficient to bind and activate expression of DhDFR and DhANS , respectively, in PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct interactions of MYB or bHLH alone with promoters of structural genes has not been previously shown. Rather, they regulate ABP structural genes by forming MBW protein complexes ( Li et al., 2021b ; Yan et al., 2021 ). Similarly, we found DhMYB2 and DhbHLH1 alone are not sufficient to bind and activate expression of DhDFR and DhANS , respectively, in PD.…”
Section: Discussionmentioning
confidence: 99%
“…MYB binding elements involved in flavonoid biosynthesis h a v e b e e n i d e n t i fi e d i n m a n y r e p o r t s , i n c l u d i n g AGMOTIFNTMYB2, MYB26PS, MYBPZM, MYB core, and MYBPLANT (Singh et al, 2015;Yan et al, 2021). Likewise, Ebox cis-acting elements are the most common binding targets of bHLH, of which G-box is the most common type (Li et al, 2021b;Qian et al, 2021). In this study, several putative ciselements recognized by MYB or bHLH were identified in the promoter regions of DhF3'H1, DhF3'5'H2, DhDFR, DhANS, and DhGT4 (Figure 6).…”
Section: Direct Interactions Between Tfs and Structural Genes Involve...mentioning
confidence: 99%
“…AtGL3 and AtEGL3 can also coordinate with MYB transcription factors to regulate the synthesis of anthocyanin but not proanthocyanidins ( Payne et al., 2000 ; Morohashi et al., 2007 ). PbbHLH2 from Pyrus bretschneideri , interacts with MYB through the N-terminal MIR domain to promote anthocyanin synthesis ( Li et al., 2021 ). Evolutionary analysis showed that ZeGL3 belonged to the GL3 clade and there was a MIR domain region present in its N-terminal ( Figure S5 ), suggesting that this protein may possess positive regulation on anthocyanin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The bHLH, R2R3-MYB, and WD repeat proteins can form a ternary MBW complex to modulate the expression of anthocyanin biosynthesis-related genes. Previous studies have revealed that several bHLH TFs, including AtTT8, AtGL3, AtEGL3, PhAN1, PhJAF13, GhMYC1, SlAN1, MdbHLH3, and PbbHLH2, interact with their respective MYB partners AtPAP1, AtTT2, PhAN2, GhMYB10, SlAN2, MdMYB1, and PbMYB9/10/10b to regulate anthocyanin or proanthocyanidin biosynthesis in Arabidopsis , Petunia hybrida , Gerbera hybrida , S. lycopersicum , M. domestica , and Pyrus bretschneideri ( Elomaa et al, 2003 ; Koes et al, 2005 ; Ramsay and Glover, 2005 ; Xie et al, 2012 ; Sun et al, 2020a ; Li et al, 2021b ). Xie et al (2012) reported that two regions (amino acids 1–24 and 186–228) at the N terminus of MdbHLH3 were crucial for the interaction between MdbHLH3 and MdMYB1.…”
Section: Discussionmentioning
confidence: 99%